2018
DOI: 10.1155/2018/9793850
|View full text |Cite
|
Sign up to set email alerts
|

Positive Antithyroid Antibodies and Nonsuppressed TSH Are Associated with Thyroid Cancer: A Retrospective Cross-Sectional Study

Abstract: The relationship between Hashimoto's thyroiditis (HT) and thyroid cancer (TC) is a controversial topic; it remains unclear if HT acts as a risk factor of TC. The aim of our study was to compare the presence of HT and thyroid function in patients with TC and benign nodules. We analyzed 2571 patients after fine needle aspiration biopsy of thyroid nodule. Totally, 91 patients with primary TC and 182 sex- and age-matched controls were included. Positive antithyroid peroxidase (anti-TPO) and antithyroglobulin (anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 23 publications
0
6
0
5
Order By: Relevance
“…This result was in line with the study of Heikkila et al (9) and Anil et al (17) However, the study of Krátký al. (19) showed that HT was found to be higher in papillary cancer compared to benign thyroid nodule. However, a study conducted by Jankovic et al (16) in population-based FNA studies did not find a statistically significant correlation between HT and PTC.…”
Section: Discussionmentioning
confidence: 99%
“…This result was in line with the study of Heikkila et al (9) and Anil et al (17) However, the study of Krátký al. (19) showed that HT was found to be higher in papillary cancer compared to benign thyroid nodule. However, a study conducted by Jankovic et al (16) in population-based FNA studies did not find a statistically significant correlation between HT and PTC.…”
Section: Discussionmentioning
confidence: 99%
“…Positive antithyroid peroxidase (anti-TPO) and antithyroglobulin (anti-Tg) antibodies were associated with TC (anti-TPO 44% in TC vs. 27% in controls, p=0.005, anti-TG 35% in TC group vs. 21% in controls, p=0.018), and the TC group had significantly higher TSH (median 1.88 mIU/L vs. 1.21 mIU/L, p<0.001). Using multiple logistic regression, positive anti-TPO was identified as an independent risk factor (OR 2.21, p=0.018), while spontaneously suppressed TSH<0.5 mIU/L was a protective factor (OR 0.3, p=0.01) against TC [32].…”
Section: Discussionmentioning
confidence: 99%
“…Thirdly, equivocal-favorable versus unfavorable-is the impact of HT on the prognosis of concurrent PTC [39][40][41][42][43][44][45][46][47][48]. Finally, the translation of the serum concentrations of thyroid autoantibodies [49-56] and thyroid-stimulating hormone (TSH) [55, [57][58][59][60][61][62][63] into predictive and prognostic PTC biomarkers incites a perpetual conflict.…”
Section: Rationality In the Investigation Of The Interrelationship Ofmentioning
confidence: 99%
“…In particular, the positivity of TPOAbs [49,52,53], TgAbs [51,53,110], as well as TPOAbs coexistent with TgAbs [52], has been shown to harbor a predictive value. Moreover, the positivity of TPOAbs [52,57] and TgAbs [50-53, 110] has been designated as an independent predictive factor for thyroid malignancy in nodular goiter. Interestingly, the coexistence of TgAbs and TPOAbs is associated with a PTC risk greater than that connected with isolated positivity of either TgAbs or TPOAbs [52].…”
Section: Thyroid Autoantibodies In the Context Of Ht Coexistent With mentioning
confidence: 99%